2017
DOI: 10.1021/acs.jpcc.7b05520
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Self-Powered Photodetector and Recoverable Photocatalyst Fabricated from Vertically Aligned Sn3O4 Nanoflakes on Carbon Paper

Abstract: Self-powered photodetectors (SPPDs) are promising candidates for high-sensitivity and high-speed applications because they do not require batteries as an external power source. It is a challenge to fabricate visible-light photodetectors. Herein, vertically aligned two-dimensional (2D) Sn 3 O 4 nanoflakes on carbon fiber paper were prepared by a modified hydrothermal approach and used as a self-powered photoelectrochemical cell-type visible-light detector. The detector exhibits reproducible and flexible propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The maximal photocurrent density of Sn-2 is over 200 μA cm −2 , about four times larger than that of sample Sn-1. This value is much larger than ever reported self-powered photodetectors (SPPDs) [28], 75 μA cm −2 in SnO x [29] and 60 μA cm −2 in Sn 2+ -SnO 2 composites [30]. To investigate the changes of the electrochemical specific surface area, the difference in current density variation plotted against scan rate is shown in figure 4(b).…”
Section: Resultsmentioning
confidence: 77%
“…The maximal photocurrent density of Sn-2 is over 200 μA cm −2 , about four times larger than that of sample Sn-1. This value is much larger than ever reported self-powered photodetectors (SPPDs) [28], 75 μA cm −2 in SnO x [29] and 60 μA cm −2 in Sn 2+ -SnO 2 composites [30]. To investigate the changes of the electrochemical specific surface area, the difference in current density variation plotted against scan rate is shown in figure 4(b).…”
Section: Resultsmentioning
confidence: 77%
“…[ 25,26 ] It is clear that O 1s contains three oxygen peaks (Figure 2D), in which O1 at around 530 eV is the lattice oxygen from TiO 2 and Sn 3 O 4 (529.9 eV for OTi or OSn 2+ and 530.4 eV for O‐Sn 4+ ), O2 (531.6 eV) is associated with the hydroxyl groups, and O3 (532.4 eV) is attributed to the oxygen defect species. [ 27–29 ] It is clear that the area ratio of O3 in Sn 3 O 4 /TiO 2 /Au is larger than that in TiO 2 /Au (Figure S7B, Supporting Information), illustrating the abundant catalytic active sites in Sn 3 O 4 cocatalyst. Thereby, it can be concluded that the TiO 2 nanorods were successfully decorated with 2D Sn 3 O 4 nanoflake cocatalysts.…”
Section: Methodsmentioning
confidence: 99%
“…Sn 3 O 4 nanoakes (NFs) were prepared on the carbon ber papers by a modied hydrothermal approach, which is similar to the reported in our previous study. 26 In detail, 1.073 g of SnCl 2 $2H 2 O and 2.940 g Na 3 C 6 H 5 O 7 $2H 2 O were dissolved in the mixture of 20 mL de-ionized water and 20 mL alcohol under constant magnetic stirring for approximately 60 min. The obtained homogeneous solution was transferred into a Teon liner of 50 mL capacity with the carbon ber paper vertical immersed into the reaction solution and keeping sealed under 180 C for 18 h. Aer the reaction, the carbon ber paper coated with a brown product was further washed with deionized water and absolute ethanol for several times.…”
Section: Synthesis Of Sn 3 O 4 Nfsmentioning
confidence: 99%
“…The energy band of Sn 3 O 4 NFs has been discussed previously. 22 Then, the conduction band and valence band (vs. vacuum) of TiO 2 NRs and Sn 3 O 4 NF scan be obtained, as shown in Table 1.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation